Silent Treatment as Emotional Violence in Domestic Violence: A Study of Victims in Plakpak Village - Aulia Agustini (At-Tafkir, 2026)
Emotional violence in domestic relationships often receives less legal and scholarly attention than physical violence, despite its profound psychological consequences. One of its most subtle yet harmful manifestations is the silent treatment, a pattern of intentional communication withdrawal used to punish, manipulate, or control a spouse. Although this behavior is increasingly recognized as a form of emotional abuse, limited empirical research has examined its occurrence and legal implications within the Indonesian context. This study aims to identify the forms of silent treatment experienced by victims of domestic violence in Plakpak Village, analyze its psychological and emotional impacts, and examine its legal relevance under Law Number 23 of 2004 on the Elimination of Domestic Violence. The research employed a qualitative case study approach conducted in Plakpak Village between February and March 2026. Data were collected through observation, in-depth interviews, and document analysis involving 25 informants, including victims, local residents, village officials, and community leaders. The findings reveal that silent treatment commonly manifests as intentional silence, communication withdrawal, emotional neglect, refusal to engage in dialogue, and social exclusion within marital relationships. These practices result in psychological distress, including anxiety, emotional insecurity, diminished self-esteem, prolonged emotional suffering, and marital instability. The study further finds that these behaviors constitute psychological violence as defined under Law Number 23 of 2004, although they are frequently normalized as private marital conflicts and therefore remain underreported and inadequately addressed by law enforcement and community institutions. The findings highlight the need to strengthen legal awareness, improve institutional responses to non-physical forms of domestic violence, and promote greater recognition of silent treatment as a serious form of emotional abuse within Indonesia's domestic violence prevention framework.